A Comprehensive Review of Chronobiological Challenges of the Sleep-Wake Cycle in Space: Implications for Long-Duration Space Missions and Translational Applications in Terrestrial Medicine (Bangladesh Pharmaceutical Journal, 2025)
Maintaining a healthy sleep-wake cycle is vital for the health and performance of astronauts on longduration space missions. The unique session type induced by space environments (high levels of microgravity and the absence of a day-night cycle) disrupts physiological circadian rhythms and adversely affects health status primarily through sleep disturbances and cognitive impairments that lead to reduction in performance. This review discusses the chronicles made by the astronauts in the space like the reflection of sleep-wake cycle disturbances with their mechanisms and biological and psychological effects of the astronauts due to these disturbances. It also discusses current countermeasures such as manipulation of exposure to light, pharmacological interventions, exercise regimens and behavioral strategies to mitigate these effects. The review emphasizes the importance of personalized and multimodal approaches for enhancing astronaut health during missions. Moreover, space research has potential applications to terrestrial medicine, especially in the management of sleep disorders and circadian rhythm misalignment in non-astronaut populations.Bangladesh Pharmaceutical Journal 28(2): 240-249, 2025 (July)